Comprehensive Molecular Diagnosis of α- and β-Thalassemia with Immunological Assessment of HBV/HCV Co-Infections in Transfusion among Iraqi Patients - Al-Saad, Nktel; Al-Mousawi, Haider; Mahdi, Salih; Al-Bderee, Mushtaq; Hasan, Ghazwan; Khikani, Ali (Bangladesh Journal of Infectious Diseases, 2026)
Background: The alpha globin (HBA1F) and the beta globin (HBB) are the causative genes for thalassemia. The hepatitis B (HBV) and hepatitis C (HCV) are two viral infections that inflame the liver. Objective: The current study was planned to detect the thalassemia patients in both molecular and immunological aspects. Methodology: This case-control study that included 24 β-thalassemia patients and 10 healthy controls (both male and female, aged 10-35 years) who were admitted to thalassemia center at Babylon Governorate from March to December 2025. β-thalassemia was diagnosed by hemoglobin electrophoresis, and genomic DNA of the HBB and HBA1F genes was analyzed by conventional PCR. HBV and HCV infections were identified immunologically, and in silico molecular docking was used to investigate the interactions between BCL11A and hemoglobin inducers hydroxyurea and resveratrol. Results: Conventional PCR was used to confirm the presence of HBB gene in 100 % of the β-thalassemic patients and the absence of HBA1F gene in α-thalassemic patients. Patients showed elevated HbA2 (2.7–6.6%) and HbF (12.1%) versus normal ranges (2–3% and 0.8–2%), with >90% identified as carriers. Eleven samples (40.0%) were positive for HCV infection by immunological assays. The binding affinities of molecular docking with hydroxyurea and resveratrol were found to be strong with BCL11A, indicating increased expression of HbF and decreased severity of the disease. Conclusion: β-thalassemia showed a high hemoglobin F (HbF) levels by HB electrophoresis test, and over most of the thalassemia patients contract the hepatitis C virus while receiving blood transfusions. Bangladesh Journal of Infectious Diseases, December 2025;12(2):234-242